Perception in young adult romantic relationships: a latent profile analysis of trait mindfulness in relation to attachment and attributions - Kimmes, Jonathan Gene (Kansas State University, 2016)
Perceptions regarding the causes and intentions behind partner transgressions are often just as important as the transgressions themselves. Although mindfulness-based interventions have been useful in clinical work with couples, the potential role that mindfulness plays in attributions is unclear. Using a sample of 542 young adults in romantic relationships, I explored the direct and indirect associations among attachment, trait mindfulness, and attributions. Specifically, I conducted a latent profile analysis, a person-centered approach, through which I identified four latent classes of trait mindfulness, including a High Mindfulness class, a Nonjudgmentally Aware class, a Low Mindfulness class, and a Judgmentally Observing class. I then ran a path analysis and found a number of significant direct effects. For example, relative to membership in the Low Mindfulness, membership in the High Mindfulness class and the Nonjudgmentally Aware class were associated with more benign attributions. I also found two significant indirect effects. First, heightened attachment anxiety was associated with an decreased probability of being Nonjudgmentally Aware class relative to the Low Mindfulness class, which was inversely linked with benign attributions. Second, avoidant attachment was linked with a decreased probability of membership in the High Mindfulness class relative to the Low Mindfulness class, which was linked to a decrease in benign attributions. The clinical implications and areas for future research based on the findings of this study are discussed.
Keywords: Romantic Relationships; Attachment; Attributions; CouplesMindfulness